Opportunities and Challenges for Regional Economic Integration in the Indian Ocean. Issue 1 (April 2019) - Wignaraja, Ganeshan; Collins, Adam; Kannangara, Pabasara
Abstract: This article examines increasing regional economic integration in the Indian Ocean, along with the region's rising importance in the global economy and outlines the challenges to greater regional integration. It finds that the strategically located Indian Ocean economy has become an increasingly important part of the global economy in the past two decades and has become more integrated within itself. Forecasts suggest that the Indian Ocean economy will likely account for around a fifth of global GDP by 2025 and its GDP per capita is expected to almost double. However, realising this outlook will depend on tackling several pressing challenges to regional integration, including improving port quality and logistics, lowering barriers to trade and investment, narrowing development gaps, and strengthening the regional economic governance. Tackling these challenges requires a combination of coherent national and regional policy measures. JEL Codes: F150, F410, F550